From Citation to Keyword Search: How Digitization Transformed the Legal Research - Yaranal, Mahesh A. (Journal of Information and Knowledge, 2015)
The Article Seeks to Examine Whether Digitization has made Legal Research Faster whereby it Leads to Greater Availability of Updated Information. it Goes on to Describe some of the Practical Limitations of Digitization. and also Narrates the Advantages of Digitization in the Light of Inter Disciplinary Works. in the Conclusion the Author has Examined the Breadth Versus Depth of Legal Research.